Biosimilar SB15 versus reference aflibercept in neovascular age-related macular degeneration: 1-year and switching results of a phase 3 clinical trial - Se Joon Woo; Srinivas R Sadda; Min Sagong; Cheolmin Yun; Edward Wylegala; Sunil Patel; Miroslav Veith; Jan Ernest; Jan Studnička; Attila Vajas; Inkyung Oh; Mario Bradvica; et al. (BMJ Open Ophthalmology, 2023)
Background/aims To evaluate efficacy, safety, pharmacokinetics (PK) and immunogenicity of SB15 versus reference aflibercept (AFL), and switching from AFL to SB15 in neovascular age-related macular degeneration (nAMD).Design Prospective, double-masked, randomised, phase 3 trial.Methods Participants with nAMD were randomised 1:1 to receive SB15 (N=224 participants) or AFL (N=225). At week 32, participants either continued on SB15 (SB15/SB15, N=219) or AFL (AFL/AFL, N=108), or switched from AFL to SB15 (AFL/SB15, N=111). This manuscript reports 1-year and switching results of secondary efficacy endpoints such as changes from baseline to week 56 in best-corrected visual acuity (BCVA), central subfield thickness (CST, from internal limiting membrane (ILM) to retinal pigment epithelium), and total retinal thickness (TRT, from ILM to Bruch’s membrane). Additional endpoints included safety, PK and immunogenicity.Results Efficacy results were comparable between groups. The least squares mean (LSmean) change in BCVA from baseline to week 56 was 7.4 letters for SB15/SB15 and 7.0 letters for AFL/AFL (difference (95% CI)=0.4 (−2.5 to 3.2)). The LSmean changes from baseline to week 56 in CST and TRT were −119.2 µm and −132.4 µm for SB15/SB15 and −126.6 µm and −136.3 µm for AFL/AFL, respectively (CST: difference (95% CI)=7.4 µm (−6.11 to 20.96); TRT: difference (95% CI)=3.9 µm (−18.35 to 26.10)). Switched and non-switched participants showed similar LSmean changes in BCVA from baseline to week 56 (AFL/SB15, 7.9 letters vs AFL/AFL, 7.8 letters; difference (95% CI)=0.0 (−2.8 to 2.8)). Safety, PK and immunogenicity were comparable between groups.Conclusions Efficacy, safety, PK and immunogenicity were comparable between SB15 and AFL and between switched and non-switched participants.